Association between Anthropometric Measures and Bone Mineral Density: Population-Based Study - HR Aghaei Meybodi; M Hemmat-abadi; R Heshmat; M Rezaei Homami; S Madani; M Ebrahimi; H Adibi; B Larijani (Tehran University of Medical Sciences, 2011)
"nBackground: Osteoporosis is a major public health concern around the world. It has been shown that bone mineral density is correlated to anthropometric measures like height and weight, but this association may vary depending on ethnic and environmental factors. The aim of this study was to identify probable relations between anthropometric measures and bone mineral density."nMethods: In this population-based study, we compiled the data collected from Iranian Multicenter Osteoporosis Study to assess the possible associations between different anthropometric indices and bone mineral density at femur and lumbar spine. The gathered data was analyzed using t-test and one way ANOVA."nResults: Data was available for 4445 subjects, consisting 1900 males (42.7%) and 2545 females (57.3%). We observed statistically significant correlations between bone mineral density and height, weight, waist circumference, hip circumference, waist to hip ratio and body mass index (BMI). Based on the result of linear regression modeling studies, BMI could be considered an independent predictor of bone mineral density."nConclusion: Iranian population shows similar measures compared to analogous studies in other populations. Lower weight should be carefully considered as a predisposing factor for bone loss and osteoporosis.